2021
DOI: 10.3758/s13415-021-00936-3
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effects of oxytocin on “mind-reading” in healthy males

Abstract: The neuropeptide oxytocin (OT) has been associated with a broad range of human behaviors, particularly in the domain of social cognition, and is being discussed to play a role in a range of psychiatric disorders. Studies using the Reading The Mind In The Eyes Test (RMET) to investigate the role of OT in mental state recognition reported inconsistent outcomes. The present study applied a randomized, double-blind, cross-over design, and included measures of serum OT. Twenty healthy males received intranasal plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…However, authors have been reluctant to suggest that the outcome of Domes et al may be a false positive. Rather, Macchia et al proposed that ‘Given that similar study designs lead to heterogeneous outcomes, our results highlight the complexity of OT effects’ [ 59 , p. 112]. Radke & de Bruijn [ 60 ], in their attempt to replicate Domes et al, found that ‘Oxytocin did not affect mind-reading, neither in general nor when considering specific item characteristics’ (p. 75).…”
Section: Partitioning the Citation Networkmentioning
confidence: 54%
See 1 more Smart Citation
“…However, authors have been reluctant to suggest that the outcome of Domes et al may be a false positive. Rather, Macchia et al proposed that ‘Given that similar study designs lead to heterogeneous outcomes, our results highlight the complexity of OT effects’ [ 59 , p. 112]. Radke & de Bruijn [ 60 ], in their attempt to replicate Domes et al, found that ‘Oxytocin did not affect mind-reading, neither in general nor when considering specific item characteristics’ (p. 75).…”
Section: Partitioning the Citation Networkmentioning
confidence: 54%
“…Other replications of Domes et al have had mixed outcomes [ 58 ]; recently, Macchia et al [ 59 ] reported that subjects performed worse after oxytocin than after placebo. However, authors have been reluctant to suggest that the outcome of Domes et al may be a false positive.…”
Section: Partitioning the Citation Networkmentioning
confidence: 99%
“…The present study was part of a larger project examining the effects of intranasally administered OT on different behavioral metrics in healthy males [ 34 ]. Due to the overall design of the project, participants of the present study had three randomized study visits (separated by at least 7 days), of which one was the experimental condition (active OT, see below for protocol of OT administration) and two were summarized as the control condition.…”
Section: Methodsmentioning
confidence: 99%
“…However, accompanying this excitement are welljustified critiques. These include the following: (i) our understanding of how oxytocin modulates social cognition is lacking in methodological rigour [14][15][16][17]; (ii) the effects of oxytocin treatment can be highly context-dependent [18,19]; (iii) we are still building a mechanistic understanding for how oxytocin impacts social behaviours at the neurobiological level [9,[20][21][22][23][24]; (iv) developmental and life experience can drastically change the function of oxytocinergic systems [25][26][27]; and (v) we lack a single overarching theory to predict how oxytocin may modulate behaviour [28][29][30][31]. These critical examinations are fundamental for advancing our understanding of oxytocin, enabling the utilization of oxytocinergic mechanisms as a means to study the neurobiology of social behaviours [32,33] and as a curative tool to restore the deficits in social cognition observed across a variety of psychiatric disorders [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the field is already successfully moving in the direction of examining oxytocin function under more naturalistic contexts and more holistically, aided by advancements in technology [ 46 , 47 ] and decades of critical introspection in the literature [ 14 , 15 , 17 , 48 ]. For example, recent research has identified supralinear enhancements of social gaze from combinatorial treatment of oxytocin and the opioid antagonist naloxone [ 49 ], demonstrating a mechanistic link between the oxytocinergic and opioidergic systems in the regulation of social attention.…”
Section: Introductionmentioning
confidence: 99%